EVALUASI GEOMETRIK, KINERJA DAN PERKERASAN LENTUR JALAN RAYA GUMITIR KABUPATEN JEMBER - Abdi Zulkarnain; Irawati Irawati; Taufan Abadi (Universitas Muhammadiyah Jember, 2019)
Gumitir highway is a class I highway as a cross road between regencies and cities (Jember - Banyuwangi). The condition of this highway field with a width of 7 meters and winding and there are slopes. This highway is passed by heavy vehicles which can cause overloading (tonnage) loading, damage to the road body. Under these conditions a geometric evaluation (of the length of the arch) and calculation of the thickness of the flexible pavement on the Gumitir highway in Jember Regency .. This study aims to (1) analyze the performance of the Gumitir highway, (2) analyze the geometric of the Gumitir highway STA 229 + 664 - STA + 019, (3) analyzing the flexible pavement conditions with the 2013 UR 20-year bina marga method, (4) analyzing the inventory of the Gumitir highway. The research was conducted using the Full Circle method to calculate the geometric conditions of the Gumitir highway and 2013 Bina Marga UR 20 method for calculating the thickness of the pavement thickness of the Gumitir highway. The results of the 2013 Bina marga pavement thickness calculation results obtained for a flexible pavement thickness of 44 cm, a 3 cm HRS WC, a 3.5 cm HRS Base, a 25 cm LPA Class A and LPA Class B 12.5 cm. The results of planning the addition of warning signs point obtained 8 electric poles, 10 street lighting lamps, 8 traffic signs (addition 8 points) and longitudinal road markings in the form of solid lines